2015
DOI: 10.1002/2015sw001170
|View full text |Cite
|
Sign up to set email alerts
|

Using the maximum X-ray flux ratio and X-ray background to predict solar flare class

Abstract: Key Points:• To show the connection between X-ray flare class and background level • To show the usefulness of the X-ray background and ratio in flare prediction • To build a framework for an X-ray flare forecast using the GOES satellite Abstract We present the discovery of a relationship between the maximum ratio of the flare flux (namely, 0.5-4 Å to the 1-8 Å flux) and nonflare background (namely, the 1-8 Å background flux), which clearly separates flares into classes by peak flux level. We established this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…We find that the normalization factor scales with SSN, which is highest when SSN is highest. Winter and Balasubramaniam (2015) found that the slope is flatter at lower solar activity levels. In the highest SSN bins, the fits were less reliable (high reduced χ 2 ).…”
Section: X-ray Flare Ratesmentioning
confidence: 95%
See 2 more Smart Citations
“…We find that the normalization factor scales with SSN, which is highest when SSN is highest. Winter and Balasubramaniam (2015) found that the slope is flatter at lower solar activity levels. In the highest SSN bins, the fits were less reliable (high reduced χ 2 ).…”
Section: X-ray Flare Ratesmentioning
confidence: 95%
“…However, for SSN > 200, the slopes appear consistent in Figure 3. As in Winter and Balasubramaniam (2015), we expect additional differences in the normalization factors and slopes for the flare rates between the solar cycles. For instance, we had shown that the normalization varied by up to ≈ 10 % and the slope varied by 9 % (solar maximum) to 16 % (rising phase) between SC 22, 23, and 24.…”
Section: X-ray Flare Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical distribution of solar flare classes is well described by a power law behaviour, with spectral index of about 2.1 and percent-level variations in slope across different solar cycles. According to the recent review by Winter & Balasubramaniam (2015), one would expect to see at least 20 solar flares with class M1 or above per month during a solar maximum period. Together with our conservative estimate of the total overlapping live time of two months for STIX and MiSolFA, this implies that there should be at least 40 observations suitable for directivity measurement.…”
Section: Expected Number Of Good Flaresmentioning
confidence: 99%
“…However, the forecasting of future X-ray background level is important because that can also impact communication devices used on Earth. Besides that, background levels can also be used for solar flare forecasting [3]. There are two main approaches used to forecast solar flares: (1) forecasting with statistical methods based on data probability distribution; (2) forecasting with data mining techniques.…”
Section: Related Workmentioning
confidence: 99%